The appearance of rabbit skin tissue (Oryctolagus cuniculus) after supplementation of Aloe vera and Spirulina fusiformis - YASMI PURNAMASARI KUNTANA; HUSMY YURMIATI; ASRI PENI WULANDARI; FARIDA SYAFITRI; RUHYAT PARTASASMITA (Smujo International, 2017)
Kuntana YP, Yurmiati H, Wulandari AP, Syafitri F, Partasasmita R. 2017. The appearance of rabbit skin tissue (Oryctolagus cuniculus) after supplementation of Aloe vera and Spirulina fusiformis. Nusantara Bioscience 9: 268-274. The research is about the appearance of rabbit skin tissue (Oryctolagus cuniculus L.) after supplementation of Aloe vera L. and Spirulina fusiformis Vor. has been done. This study was carried out to find the most effective formulation ofsupplement of A. vera and S. fusiformis as a natural supplement that can generate the best appearance of rabbit skin tissue. The method in this research was a single Complete Random Design (CRD) on 28 male New Zealand White strains rabbits with the age of 16 weeks. The treatments were divided into seven groups with four replications, namely, P0 (negative control ), P1(positive control, vitamin C19 mg/kg BW), P2 (A. vera 74 mg/kg BW), P3 (S. fusiformis 296 mg/kg BW), P4 (A. vera: S. fusiformis, 74: 148 mg/kg BW), P5 (A. vera: S. fusiformis, 74: 296 mg/kg BW), and P6 (A. vera: S. fusiformis, 74: 593 mg/kg BW). The parameters observed were production aspect (hair texture, slaughter weight, skin width, and skin weight percentage) and histological aspect (thickness of skin tissue and the amount of hair follicle). All of the data was analyzed using ANOVA test (P Ëƒ 95%) and Duncan test (P Ëƒ 95%). The result showed that the giving of supplement with the basis of the formulation of A. vera 74 mg/kg bw and S. fusiformis 296 mg/kg bw was effective in generating the best appearance of rabbit skin tissue.